Appointment Adherence to a City-Wide Cardiovascular Disease Prevention Program: Its Predictors and Outcomes. (July 2021) - Choo, Jina; Yang, Hwa-Mi; Park, Sooyeon; Park, MiSuk; Park, Yoo Mi; Lim, Do-Sun
This study identified predictors of appointment adherence and examined its impacts on improvements in metabolic risk factors in a free city-wide cardiovascular disease prevention program in Seoul, South Korea. Data of 8251 citizens with metabolic syndrome were used. Appointment adherers were defined as having 70% or higher adherence rates, that is, 3 or more visits. Of the 8251 citizens, 17.6% were appointment adherers. Appointment adherers were significantly more likely to be older, low-income earners, nonsmokers, and nonobese than appointment nonadherers. Moreover, appointment adherers, compared with nonadherers, showed significant improvements in waist circumference, systolic blood pressure, and high-density lipoprotein cholesterol, but not in fasting glucose and triglycerides. Designing strategies for increasing appointment adherence to a free city-wide cardiovascular disease prevention program is essential to improve health outcomes, especially targeting population groups with young age, high-income, current smoking, or obesity.